2006
DOI: 10.1136/bjo.2005.076190
|View full text |Cite
|
Sign up to set email alerts
|

Cell viability effects of triamcinolone acetonide and preservative vehicle formulations

Abstract: Aim: To assess the effect of triamcinolone acetonide and preservative vehicle formulations on human retinal pigment epithelium (ARPE19) cells over a range of concentrations. Methods: Triamcinolone acetonide, in its trade and preservative free formulations, along with the preservative vehicle were added to ARPE19 cell cultures in various concentrations (0.01-1.0 mg/ml). Cell viability was assessed using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay at day 5 after exposure. Functionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 17 publications
2
24
0
3
Order By: Relevance
“…Because these areas were positive for GFAP and vimentin, we interpreted them as areas of Müller end-foot cell hypertrophy. Although we removed most of the preservative present in the commercial preparation of triamcinolone as previously described, 88 the substance or the remaining preservative may have cellular toxic effects, 88,89 and the retina may react to stress with the initiation of glial blooms or preretinal membranes as has been observed in degenerating retinas. 87,90,91 On the other hand, treatment with the anti-VEGF aflibercept and ranibizumab has been shown to activate neonatal rat Müller cells in culture, and it has been proposed that it may be responsible for the therapeutic effects of these drugs.…”
Section: Macroglial Responsementioning
confidence: 99%
“…Because these areas were positive for GFAP and vimentin, we interpreted them as areas of Müller end-foot cell hypertrophy. Although we removed most of the preservative present in the commercial preparation of triamcinolone as previously described, 88 the substance or the remaining preservative may have cellular toxic effects, 88,89 and the retina may react to stress with the initiation of glial blooms or preretinal membranes as has been observed in degenerating retinas. 87,90,91 On the other hand, treatment with the anti-VEGF aflibercept and ranibizumab has been shown to activate neonatal rat Müller cells in culture, and it has been proposed that it may be responsible for the therapeutic effects of these drugs.…”
Section: Macroglial Responsementioning
confidence: 99%
“…3) also showed that a benzyl alcohol concentration of 9 mg/mL caused extensive lysis of rabbit corneal endothelial cells within the first minute of exposure. Recently, Shaikh et al 17) showed that both the preserved TA formulation and its vehicle caused significant reductions in the viability of cultured retinal epithelial cells. Similarly, Narayanan et al 15) concluded that the vehicle was not totally responsible for toxicity but may initiate TA-dependent toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…We could further determine a safe concentration for the intravitreal injection of TA. This is of particular importance in view of recent publications regarding a cytotoxic effect of TA in vitro [56,57]. However, cytotoxicity in vitro is contradicted by good clinical biocompatibility experiences.…”
mentioning
confidence: 95%